IMPLEMENTATION OF THE TEAMS GAMES TOURNAMENT TYPE COOPERATIVE LEARNING MODEL ASSISTED WITH QUIZWHIZZER TO IMPROVE STUDENTS' COGNITIVE LEARNING OUTCOMES - Rahayu, Rati; Syahril, Syahril; Fakhruddin, Fakhruddin (JURNAL SPEKTRA, 2024)
Good education has several components that support it, starting from learning planning, learning strategies, learning media to be used, and evaluation in learning. This research aims to describe the cognitive learning outcomes of class VIII MTsS Miftahul Ulum students after implementing the TGT type cooperative learning model assisted by Quizwhizzer and to determine the significant differences in cognitive learning outcomes between classes that apply the TGT type cooperative learning model assisted by Quizwhizzer and conventional classes on aircraft simple. This type of research uses quantitative research and the sample for this research is simple random sampling. Based on the results of descriptive and inferential analysis, it was stated that the experimental class that was given treatment using the TGT type cooperative learning model assisted by Quizwhizzer received a higher average score, namely 80.47, compared to the control class using the conventional learning model with an average score of 70.31. Based on the hypothesis test that was carried out using the Independent Sample T-Test, a significance value was obtained for the sig (2-tailed) of 0.000, which means it is less than 0.05. Based on the descriptive and inferential analysis that has been carried out, it can be concluded that the application of the TGT-type cooperative learning model assisted by Quizwhizzer can improve students' cognitive learning outcomes.